Glucose oxidase-induced colorimetric immunoassay for qualitative detection of danofloxacin based on iron (Ⅱ) chelation reaction with phenanthroline. (30th October 2020) - Fang, Bolong; Xu, Shaolan; Huang, Zhen; Wang, Suhua; Chen, Wenyao; Yuan, Meifang; Hu, Song; Peng, Juan; Lai, Weihua
Highlights: Colorimetric ELISA could screen DAN with low LOD (2.5 ng mL −1 ) without instrument. There was no matrix effect with four kinds of samples using the novel method. Sharp color change decreased judgement mistakes by individual naked-eye observation. Abstract: In this study, we developed a competitive colorimetric immunoassay for qualitative detection of DAN based on oxidation of iron (Ⅱ) (Fe 2+ ) in the presence of glucose oxidase (GOx) and color change induced by Fe 2+ -phenanthroline (Phen) chromogenic system. Streptavidin (SA) acted as a linker between biotinylated anti-DAN-monoantibody (bio-mAb) and biotinylated GOx (bio-GOx) to form the immunocomplexes bio-mAb-SA-bio-GOx. In the absence of DAN, the immunocomplexes bio-mAb-SA-bio-GOx combining with coated DAN-ovalbumin (DAN-OVA) will be immobilized and catalyze glucose to produce H2 O2 . Fe 2+ is oxidized to Fe 3+ by H2 O2, giving rise to a colorless result. In the presence of DAN, Fe 2+ produces a chelation reaction with Phen, leading to orange-red color. Under optimal conditions, the detection limit (LOD) by naked eyes was 2.5 ng mL −1 in milk, chicken, beef, and pork samples. Low LOD, no matrix effect, and no signal reader requirement make it possibly applied to quickly screen DAN on site.